Effect of Yellow Propolis on Biocompatibility of Cements: Morphological and Immunohistochemistry Analysis - Meneses, Izaura Helena Chaves de; Sampaio, Gêisa Aiane de Morais; Vieira, Rayssa Amaral; Campos, Márcio José da Silva; Alves, Polliana Muniz; Pithon, Matheus Melo; Lacerda-Santos, Rogério (European Journal of Dentistry, 2021)
Objective The focus of this study was to evaluate the biocompatibility of ionomer cements modified with ethanolic extracts of propolis (EEP) in different concentrations and time intervals.Materials and Methods In total, one hundred and thirty-five male Wistar rats were randomized into nine groups: Control, Groups Meron, and Groups Ketac (conventional, and added with 10, 25, 50% EEP, respectively). Histological analyses of inflammatory infiltrate and collagen fibers, and immunohistochemistry of CD68+ for macrophages (MOs) and multinucleated giant cells (MGCs) were performed.Statistical Analysis Data were analyzed using the Kruskal—Wallis and Dunn (p < 0.05) tests.Results Intense inflammatory infiltrate was demonstrated in the cements with 10% EEP at 7 days and 15 days (p < 0.05), only Group Ketac 10% EEP (p = 0.01) at 30 days. A smaller quantity of collagen fibers was observed in the cements with 10% EEP (p = 0.01) at 7 days, and Group Meron 10% EEP (p = 0.04) at 15 days. MOs and MGCs showed significant difference for the cements with 10% EEP (p = 0.01) at 7 and 15 days. At 30 days, MOs persisted in the Groups with 10% EEP.Conclusions The concentration of 10% EEP had the greatest influence on the inflammatory and tissue repair processes. The concentrations of 25 and 50% EEP demonstrated biocompatibility similar to that of cements that did not receive EEP.
Keywords: microscope; propolis; biocompatibility; histological; glass ionomer cements